A Modern Exposition of the Determinants of Corporate Cash Holdings: Evidence From A Panel of U.S. Firms For the Period 2000 to 2015 - Dredge-Hetherington, Francis (2016)
This paper investigates the empirical determinants of corporate cash holdings for a sample of U.S. firms for the period 2000 to 2015. We focus on the key articulations of the trade-off model, the financing hierarchy model, agency theory, and the tax motive in order to explain the cash holding behavior of U.S. firms. Employing a dynamic model of cash holdings, we report that cash holding behavior of the firm is best described by a combination of the trade-off model and the financing hierarchy model. However, we find no evidence of the tax motive for holding cash, and the statistical significance of agency motives varies with the definition of cash employed. On the whole, the results reveal that firm size, leverage, cash flows, cash flow volatility, liquidity, growth opportunities, investments and derivative usage are important in determining the firm’s level of cash. Further, our analysis suggests that firm heterogeneity and endogeneity, as well as the definition of cash employed, are fundamental in analyzing the cash balances of firms.